2015
DOI: 10.3892/mmr.2015.3423
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid inhibits chondrogenesis of rat embryo hindlimb bud mesenchymal cells by downregulating p53 expression

Abstract: Despite the well-established role of all-trans-retinoic acid (ATRA) in congenital clubfoot (CCF)-like deformities in in vivo models, the essential cellular and molecular targets and the signaling mechanisms for ATRA-induced CCF-like deformities remain to be elucidated. Recent studies have demonstrated that p53 and p21, expressed in the hindlimb bud mesenchyme, regulate cellular proliferation and differentiation, contributing to a significant proportion of embryonic CCF-like abnormalities. The objective of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Interestingly, the osteogenic differentiation of MEPM cells from atRA-induced cleft palates were also weaker than MEPM cells from normal palates. We did not determine whether atRA could affect adipogenic and chondrogenic differentiation, but there are many other studies that show that atRA could block adipogenic differentiation by MEPM cells [73][74][75] and chondrogenic differentiation [76][77][78][79][80] . Our results showed that atRA regulated osteogenic differentiation through the disruption of MEPM cell stemness and pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the osteogenic differentiation of MEPM cells from atRA-induced cleft palates were also weaker than MEPM cells from normal palates. We did not determine whether atRA could affect adipogenic and chondrogenic differentiation, but there are many other studies that show that atRA could block adipogenic differentiation by MEPM cells [73][74][75] and chondrogenic differentiation [76][77][78][79][80] . Our results showed that atRA regulated osteogenic differentiation through the disruption of MEPM cell stemness and pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…DMSO alone was added to control cultures at a final concentration of 0.05% (v/v). The concentrations selected were based on a previous study [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both in vivo and in vitro studies indicate that correct levels of RA are important for normal chondrogenesis in the developing limb (Lee et al, 2004a;Underhill and Weston, 1998;Weston et al, 2003). Numerous mouse studies indicate that either excess or deficiency of RA disrupts chondrogenesis through inhibition of proliferation and differentiation of mesenchymal precursor cells (Dranse et al, 2011;Tsuiki and Kishi, 1999;Wang et al, 2014aWang et al, , 2014bZhang et al, 2015;Zhou and Kochhar, 2004). Interestingly, RA-induced cartilage defects are more severe in the forearms than in the hands indicating that RA has position-related effects (Masuda et al, 2015).…”
Section: Ra In the Development Of The Limbsmentioning
confidence: 99%